2016
DOI: 10.1016/j.neuropharm.2016.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of nucleus accumbens dopamine leads to impaired reward and aversion processing in mice: Relevance to motivation pathologies

Abstract: Dopamine (DA) neurotransmission, particularly the ventral tegmental area-nucleus accumbens (VTA-NAcc) projection, underlies reward and aversion processing, and deficient DA function could underlie motivational impairments in psychiatric disorders. 6-hydroxydopamine (6-OHDA) injection is an established method for chronic DA depletion, principally applied in rat to study NAcc DA regulation of reward motivation. Given the increasing focus on studying environmental and genetic regulation of DA function in mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 75 publications
1
29
1
Order By: Relevance
“…The importance of this pathway for reward was demonstrated by a study that blocked dopaminergic signaling in this area. 6‐Hydroxydopamine (6‐OHDA)‐induced lesions in the NAc disrupted rewarding responses . Dopaminergic neurons in the VTA also project to the medial prefrontal cortex, and this projection is considered to play a role in aversion …”
Section: Dopamine Function and Brain Reward Systemsmentioning
confidence: 99%
“…The importance of this pathway for reward was demonstrated by a study that blocked dopaminergic signaling in this area. 6‐Hydroxydopamine (6‐OHDA)‐induced lesions in the NAc disrupted rewarding responses . Dopaminergic neurons in the VTA also project to the medial prefrontal cortex, and this projection is considered to play a role in aversion …”
Section: Dopamine Function and Brain Reward Systemsmentioning
confidence: 99%
“…It is important to point out that a deficit in PPI has been observed in many psychiatric disorders characterized by alterations in the cerebral dopaminergic system, and is thus already considered an endophenotype of schizophrenia (Swerdlow and Light, 2016). Additionally, the dopaminergic system, from the ventral tegmental area to the NAc, is considered a central circuitry for the regulation of PPI (Doherty et al, 2008;Rohleder et al, 2016) and motivation for reward and drug-seeking (Bergamini et al, 2016;Scofield et al, 2016). Therefore, we endorse PPI paradigm as a useful indicator of subjects with a higher vulnerability to the effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a common symptom in depression (DSM-5, ICD-10). Reduced treadmill running is induced by CSS [ 32 ] and by depletion of dopamine in the nucleus accumbens [ 34 ]. In contrast to the forced swim test and tail suspension test, where it is unclear whether passivity indicates an adaptive, energy-conserving strategy or a cessation of active coping [ 50 ], in the treadmill fatigue test it is clear that passivity is maladaptive and related to fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…Relative to control mice, CSS mice exhibit altered brain functional connectivity [ 31 ], increased immune-inflammation in periphery and brain in terms of pro-inflammatory cytokines and the kynurenine pathway [ 32 , 33 ], decreased motivation for reward [ 34 ], increased Pavlovian fear learning-memory [ 32 , 33 ], increased learned helplessness [ 32 ], and increased physical fatigue [ 32 ]. It has been demonstrated that some CSS-induced reward deficits are attenuated by the antidepressant agomelatine [ 34 ], and that CSS-induced excessive fear memory is reversed by the antidepressant escitalopram as well as by an inhibitor of the kynurenine pathway [ 33 ]. That is, CSS induces changes in behavioral processes that are recognised as important dimensions in negative valence and positive valence domains in the research domain criteria (RDoC) framework for mental disorders [ 35 ].…”
Section: Introductionmentioning
confidence: 99%